When Legal Constraints Reshape Contractual Agreements : The Example of Compulsory Insurance - ESSAFI, Asma (Revue Internationale du Chercheur, 2025)
Abstract This article explores the legal nature of compulsory insurance and challenges its traditional contractual characterization, which is based on mutual consent. In such cases, the legal constraint imposed by the State often supplants contractual freedom for both the insured and the insurer, thereby calling into question the existence of freely expressed consent. In light of this reality, the article proposes a reassessment of the concept of contract—no longer viewed solely through the lens of the parties’ will, but rather through the convergence of their reciprocal interests. It emerges that, even within a constrained framework, legal effects may arise, thereby justifying the continued classification of such arrangements as contracts. The voluntarist approach is thus partially outdated, particularly in cases where the law heavily regulates the content of the contract. An interest-based approach—whether objective or subjective—makes it possible to incorporate into contract theory hybrid or imposed situations, such as compulsory insurance. This paves the way for a renewed definition of the contract, one that also encompasses collective organizational agreements and norms arising independently of the parties’ intent.